The Impact of ICT on Economic Development in Armenia - Movsesian, Roman (2023)
The rapid development of information and communication technologies (ICTs) has transformed the world economy and society in recent decades. This thesis examines the case of the Armenian ICT sector, its current state, trends, and its impact on various sectors of the economy and society. The thesis also identifies the Armenian ICT sector's main challenges and opportunities. It provides evidence-based insights and recommendations for policymakers and investors to foster the development of the ICT sector and leverage its potential for economic development in Armenia.